Folk Toys and Games for Children: Cultural Heritage of Vietnam - Nhi, Vu Hong (International Journal of Social Sciences and Management, 2017)
Folk toys and games are elements of folklore, created by the people, which contain tangible and intangible cultures of profound value from various communities, regions, or countries. In this article the author analyzes the importance of the role of folk toys for children in educating them about their traditional culture, creative and aesthetic values, and promoting personal skills as well as community cohesion. Folk toys also contribute to the economy of many trade villages, thereby contributing to social and economic development. Int. J. Soc. Sc. Manage. Vol. 4, Issue-4: 223-231